Linking Auxin with Photosynthetic Rate via Leaf Venation. Issue 1 (21st July 2017) - McAdam, Scott A.M.; Eléouët, Morgane P.; Best, Melanie; Brodribb, Timothy J.; Murphy, Madeline Carins; Cook, Sam D.; Dalmais, Marion; Dimitriou, Theodore; Gélinas-Marion, Ariane; Gill, Warwick M.; Hegarty, Matthew; Hofer, Julie M. I.; et al.
Abstract : Auxin influences maximum leaf photosynthetic rate through leaf venation and thus water transport capacity. Abstract: Land plants lose vast quantities of water to the atmosphere during photosynthetic gas exchange. In angiosperms, a complex network of veins irrigates the leaf, and it is widely held that the density and placement of these veins determines maximum leaf hydraulic capacity and thus maximum photosynthetic rate. This theory is largely based on interspecific comparisons and has never been tested using vein mutants to examine the specific impact of leaf vein morphology on plant water relations. Here we characterize mutants at the Crispoid ( Crd ) locus in pea ( Pisum sativum ), which have altered auxin homeostasis and activity in developing leaves, as well as reduced leaf vein density and aberrant placement of free-ending veinlets. This altered vein phenotype in crd mutant plants results in a significant reduction in leaf hydraulic conductance and leaf gas exchange. We find Crispoid to be a member of the YUCCA family of auxin biosynthetic genes. Our results link auxin biosynthesis with maximum photosynthetic rate through leaf venation and substantiate the theory that an increase in the density of leaf veins coupled with their efficient placement can drive increases in leaf photosynthetic capacity.